Emamectin benzoate: A novel second generation avermectin derivative for management of biotic stress in lac culture through treatment of broodlac - JAISWAL, A K; SINGH, J P; PATAMAJHI, P (The Indian Journal of Agricultural Sciences, 2017)
Experiment was conducted to evaluate the safety of emamectin benzoate, against lac insect [Kerria lacca (Kerr)] and bio-efficacy against associated lepidopteran predators in lac culture. Seven concentrations of emamectin benzoate (5% SG) ranging from 0.00025 % a.i. (0.05 g/L) to 0.0030 % a.i. (0.6 g/L) were evaluated by dipping of broodlac (functional seed of lac culture) in insecticidal formulation for 5, 10 and 15 min durations. Non-significant differences amongst various treatments and control on survival of settled second instar larvae and adult female lac insect clearlyindicated the safety of insecticide on lac insect. Treatment of broodlac in insecticidal formulations (0.00025, 0.0005, 0.0010, 0.0015, 0.0020, 0.0025 and 0.0030 % a.i.) for 5, 10 and 15 min durations exerted significant reduction in the population of both key lepidopteran predators, Eublemma amabilis Moore (Noctuidae) and Pseudohypatopa pulverea Meyr (Blastobasidae) harboring broodlac. The treatment of rangeeni broodlac with 0.00025 % a.i. emamectin benzoate for 10-15 min and kusmi broodlac with 0.0005 % a.i. for 5-10 min duration provides effective tool for the management of both major lepidopteran predators of lac insects. This novel insecticide can be safely and effectively integrated inIPM programme of lac production system.